2020
DOI: 10.1002/jsfa.10367
|View full text |Cite
|
Sign up to set email alerts
|

Positron‐emitting tracer imaging of fluoride transport and distribution in tea plant

Abstract: BACKGROUNDTea (Camellia sinensis (L.) O. Kuntze) is a hyper‐accumulator of fluoride (F). To understand F uptake and distribution in living plants, we visually evaluated the real‐time transport of F absorbed by roots and leaves using a positron‐emitting (18F) fluoride tracer and a positron‐emitting tracer imaging system.RESULTSF arrived at an aerial plant part about 1.5 h after absorption by roots, suggesting that tea roots had a retention effect on F, and then was transported upward mainly via the xylem and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
3
3
0
Order By: Relevance
“…Root application of the bolus confirmed the ability of [ 18 F]fluoride to enter the transpiration stream through the root tissue bypassing the endodermis. This was consistent with other studies where [ 18 F]fluoride supplied to the roots of tea (Niu et al 2020 ) and cowpea (Furukawa et al 2001 ) that also showed upward mobility into the stem and leaves. The observation that the fluoride entered both WT and fex with equally efficiency (WT: 2.9 1.4 (μCi/g)/μCi bolus, fex : 2.2 0.9 (μCi/g)/μCi bolus), suggested that the main role of FEX was not to keep fluoride out of the root tissue.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Root application of the bolus confirmed the ability of [ 18 F]fluoride to enter the transpiration stream through the root tissue bypassing the endodermis. This was consistent with other studies where [ 18 F]fluoride supplied to the roots of tea (Niu et al 2020 ) and cowpea (Furukawa et al 2001 ) that also showed upward mobility into the stem and leaves. The observation that the fluoride entered both WT and fex with equally efficiency (WT: 2.9 1.4 (μCi/g)/μCi bolus, fex : 2.2 0.9 (μCi/g)/μCi bolus), suggested that the main role of FEX was not to keep fluoride out of the root tissue.…”
Section: Resultssupporting
confidence: 93%
“…The source buffer showed negligible loss of radioactivity after administration. These results were consistent with observations made with larger plants which established that movement of [ 18 F]fluoride bolus within plant tissues could be monitored by PET ( Glycine max , McKay et al 1988 ; rice, Kang et al 2009 ; Brassica oleracea , Converse et al 2015 ; tea, Niu et al 2020 ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Most fluoride taken up by tea roots is readily transported through the xylem as F − and F–Al complexes to the leaves, 42 where it is retained in the cell wall or vacuole in the form of F–Al complexes, 43–45 or less prevalent F–Ca complexes, 45 consistent with other hyperaccumulator plants 46,47 . Furthermore, the exogenous addition of calcium and amendments (charcoal or bamboo charcoal) significantly decreases fluoride concentration in tea leaves through reducing the amount of available fluoride in soil, staying in the roots as F–Ca complexes or affecting the properties of leaf cell wall and membrane permeability 48,49 …”
Section: Absorption Transportation and Accumulation Of Fluoride In mentioning
confidence: 99%
“…Positron emission tomography (PET) is a non-invasive technology for radionuclide imaging, and it is sensitive to and informative of biological processes in vivo . A significant advantage of PET technology is that it is non-invasive, and that this powerful tool has been used not only for the diagnosis of various cancers ( Phelps, 2000 ) but also the study of plant science ( McKay et al, 1988 ; Kang et al, 2009 ; Niu et al, 2020 ), bacterial infections ( Northrup et al, 2019 ; Welling et al, 2019 ) and even the subsurface microbial processes of soils ( Kinsella et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%